A Case of Nonsyndromic Aplasia Cutis Congenita (Epitheliogenesis Imperfecta) in a Large White Yorkshire Piglet (Indian Journal of Animal Production and Management, 2024)
Nonsyndromic Aplasia Cutis Congenita  (Epitheliogenesis Imperfecta) are congenital,  circumscribed hypoplastic defects of multiple or  deeper skin layers in swine. Although swine have  been reported to have epitheliogenesis imperfecta,  little is known about this condition in the literature.  A new born Large White Yorkshire female piglet  was presented with glistening red, well-demarcated  discontinuities in the skin on the frontal skull with no  apparent bleeding which was managed by  conservative treatment.
Keywords: Aplasia Cutis Congenita; Large White Yorkshire piglet; skin anomaly